The Effectiveness Of Motion Graphic In Learning Chinese Character Stroke Order Through Cognitive Load Theory Assessment - Cao, Wenjun (2023)
This research aimed to investigate the effects of CCSOMG on students' learning performance and cognitive load. The Chinese character strokes are numerous and complex. Memorising the Chinese character stroke order is a major challenge for non-native language learners. To this end, this research developed and evaluated six CCSOMG for non-native language learners to remember the Chinese character stroke order. The six CCSOMG were developed by adopting the cognitive load theory as the important theoretical grounding and the ADDIE model as the instructional design framework and implemented in the language classes at the USM School of Languages, Literacies, and Translation. A proper experimental design was used to conduct this study. Forty participants were randomly divided into the experimental group (CCSOMG method, N=20) and the control group (traditional teaching method, N=20). Statistical analysis was performed on the learning performance of the two groups using independent samples T-test, and the results showed a significant difference in the scores for the two groups. The learning performance of the experimental group was better than that of the control group. Then the cognitive load of the two groups of students was measured with the subjective rating scale. Statistical analysis of the mental effort and material difficulty of the two groups using the Mann-Whitney U test showed a significant difference in scores between the two groups. The learners who used CCSOMG exerted much less mental effort and felt much less material difficulty than those who used the traditional method.